The An Understanding of How Stakeholder Relationships May Affect the Reputation of a Corporation - Clement Lee Wei Siang (Tecno Scientifica Publishing, 2022)
This study aimed to examine the relationship between stakeholder relationships and a company's reputation in the field of public relations. Responses from industry stakeholders in public relations were analyzed using an interview-based qualitative research technique. There were a few particular aspects that were examined in terms of corporate reputation, such as stakeholder management, stakeholder communication, stakeholder power analysis, corporate reputation, mutual trust, and reputation and stakeholders. From the study, it was discovered that trust between the corporation and its stakeholders creates value and loyalty for better and stronger strategic decision-making.